1997
DOI: 10.1046/j.1365-2141.1997.2553072.x
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to continuous subcutaneous infusion of desferrioxamine in thalassaemic patients

Abstract: Summary. Sixteen patients with thalassaemia major were treated with subcutaneous desferrioxamine (DF) 50 mg/kg/d, 5 consecutive days a week, for 8 weeks. Every other week the total dose was administered by 12 h infusion pump or by rapid injection of the same dose (25 × 2 mg/kg) twice a day. The two methods of DF administration produced no significant differences in urinary iron excretion. No significant changes in serum ferritin levels were observed at the end of the study. Compared with continuous infusion, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…When evaluating the immediate efficacy of both regimens of DFO administration by measurements of UIE, we found no significant difference. Our observations were confirmed later in 16 patients with -thalassemia major by Di Gregorio et al [46]. It was also reported that all patients preferred the bolus administration, and no serious side effects were observed.…”
Section: Treatment Of Iron Overload In Mdssupporting
confidence: 87%
“…When evaluating the immediate efficacy of both regimens of DFO administration by measurements of UIE, we found no significant difference. Our observations were confirmed later in 16 patients with -thalassemia major by Di Gregorio et al [46]. It was also reported that all patients preferred the bolus administration, and no serious side effects were observed.…”
Section: Treatment Of Iron Overload In Mdssupporting
confidence: 87%
“…Though clinically effective, DFO has the drawback of having relatively high hydrophilicity, which reduces its ability to cross the lipid bilayer of cell membranes [17] and lowers its potential for absorption from the gastrointestinal tract. Consequently, the drug must be given parenterally, as a continuous subcutaneous infusion, or as a continuous intravenous infusion over long periods of time (12–24 h/day; 5–6 days/week) [18, 19]. On the other hand, ICL670 is absorbed more effectively by the intestine and also has a longer half-life than DFO [20].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other studies confirmed these findings in thalassemic and nonthalassemic iron-overloaded patients. [5][6][7][8] More recently, we documented the long-term safety and efficacy of this method in 26 iron-overloaded adult patients. 9 Since then, we have received many letters from colleagues who wanted to start such a method of administration or who asked us for an update of our patients.…”
mentioning
confidence: 99%